Two Fists in One Mouth - Zewi, Meki (Fourth Dimension Publishing Co Ltd, 1995)
This book for young people, helping them to understand that the school where you live your life. because the restriction or overprotection of parents are far away.
Keywords: Juvenile literature-Drama-Nigerian (English)